PENGARUH ZEATIN TERHADAP MULTIPLIKASI TUNAS EKSPLAN NODUS PADA TANAMAN KRISAN VARIETAS KULO DAN PUSPITA NUSANTARA - Deivi V. Saburu; Bobby Polii; Arthur Pinaria; Wenny Tilaar (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to determine the effect of zeatin on shoot multiplication of explants nodesat Kulo and Puspita Nusantara varieties of chrysanthemum plant. Characters observerdwere time of shoots formation, number of shoot, number of leaf and number of root. Theresearch was conducted in the Laboratory of the Faculty of Agriculture, University ofSam Ratulangi for three month starting from July 2015 until October 2015.The researchwas designed using a completely randomized design with four treatments. Each treatmentwas repeated three time.Data was analyzed using variance analysis and Least SignificantDifference was used to differentiate the treatment. The result showed that the Zeatintreatment was significant difference on time of shoots formation, number of shoot andnumber of root at Kulo variety. Whereas, the Zeatin treatment was not significantdifference on number of shoot and number of leaf at Puspita Nusantara variety.Application of 0,5 ppm Zeatin concentration result the highest number of shoots, numberof leaves, number of roots on Kulo and Puspita Nusantara variety. Application of 0,5 ppmZeatin concentration and control resulted the fastest of time of shoots formation on Kuloand Puspita Nusantara variety.